IDDF2022-ABS-0279 Myeloid-derived suppressor cells mobilization through CXCL1-CXCR2 signaling facilitate tumor recurrence after liver surgery. (2nd September 2022) - Wang, Yuewen; Yang, Xinxiang; Liu, Hui; Chen, Zhiwei; Man, Kwan
Abstract : Backgrounds and Aims: Liver cancer is predicted to be the sixth most commonly diagnosed cancer and the fourth leading cause of cancer death worldwide. Long-term survival for patients with hepatocellular carcinoma (HCC) is hindered by tumor recurrence. The immunosuppression regimen of the patient is a possible factor in preventing HCC recurrence, as the immune system is a major defense against cancer, either by attacking dysplastic cells themselves or by controlling viruses linked to cancer. Emerging evidence confirm myeloid-derived suppressor cells (MDSCs) accumulation in the tumor microenvironment (TME) and their immunosuppressive mechanisms in immune resistance. However, its hepatic oncogenic mechanism remains poorly defined. Here we aim to investigate the role of MDSCs subpopulations on tumor recurrence. Methods: The proportion of MDSCs in HCC patients who underwent liver resection was analyzed by immunohistochemistry and flow cytometry. The underlying mechanism was further explored in the tumor-bearing mice model and hepatic ischemia/reperfusion injury (IRI) mice model with major hepatectomy. Results: The significant enrichment of circulating MDSCs was observed in HCC recurrence patients before liver resection and at the following time points (IDDF2022-ABS-0279 Figure 1). The high proportion of circulating MDSCs was significantly associated with poor overall survival and disease-free survival (IDDF2022-ABS-0279 Figure 2). Given the role of CXCL1 in tumorigenesis, increased CXCL1 mRNA expression was associated with HCC recurrence in tumor tissues, indicating the prognostic value of CXCL1 in immune surveillance (IDDF2022-ABS-0279 Figure 3A). While in non-tumor tissues, the CXCL1 expression was positively correlated with MDSCs (IDDF2022-ABS-0279 Figure 3B), indicating MDSCs mobilization in non-tumor tissues (IDDF2022-ABS-0279 Figure 3C). Upregulated CXCL1 of the liver was also found in hepatic ischemia/reperfusion mice model with an increased proportion of M-MDSC (IDDF2022-ABS-0279 Figure 4). Moreover, a high level of CXCR2 expression was detected on PMN-MDSCs with the increased level of IL-10, especially in the HCC recurrent patients (IDDF2022-ABS-0279 Figure 5), which indicates CXCL1-CXCR2 signaling may induce MDSC mobilization. Conclusion: CXCL1/CXCR2 signaling mobilized circulating MDSCs which further promoted tumor recurrence after liver resection. The populations of circulating MDSCs may predict HCC recurrence.